Giving birth: A hermeneutic study of the expectations and experiences of healthy primigravid women in Switzerland - Fleming, Valerie; Frank, Franziska; Meyer, Yvonne; Pehlke-Milde, Jessica; Zsindely, Piroska; Thorn-Cole, Harriet; de Labrusse, Claire (PLOS ONE, 2022)
Switzerland experiences one of the highest caesarean section rates in Europe but it is unclear why and when the decision is made to perform a caesarean section. Many studies have examined from a medical and physiological point of view, but research from a women’s standpoint is lacking. Our aim was to develop a model of the emerging expectations of giving birth and the subsequent experiences of healthy primigravid women, across four cantons in Switzerland. This longitudinal study included 30 primigravidae from the German speaking, 14 from the French speaking and 14 from the Italian speaking cantons who were purposively selected. Data were collected by semi-structured interviews taking place around 22 and 36 weeks of pregnancy and six weeks and six months postnatally. Following Gadamer’s hermeneutic, which in this study comprised 5 stages, a model was developed. Four major themes emerged: Decisions, Care, Influences and Emotions. Their meandering paths and evolution demonstrate the complexity of the expectations and experiences of women becoming mothers. In this study, women’s narrated mode of birth expectations did not foretell how they gave birth and their lived experiences. A hermeneutic discontinuity arises at the 6 week postnatal interview mark. This temporary gap illustrates the bridge between women’s expectations of birth and their actual lived experiences, highlighting the importance of informed consent, parent education and ensuring women have a positive birth and immediate postnatal experiences. Other factors than women’s preferences should be considered to explain the increasing caesarean section rates.